Respon Mahasiswa terhadap media pembelajaran dengan menggunakan vidio: Respon Mahasiswa terhadap media pembelajaran dengan menggunakan vidio - Ningsih, Sekar Ayu; Sevrika, Hevriani; Siska (Yayasan Pendidikan Tanggui Baimbaian, 2024)
This study aims to describe students responses to learning media by using videos. This research used qualitative research methods. This research used random sampling technique, namely quota sampling. This research used instruments in the form of questionnaire and interviews. Respondents in this study were 27 students in English Education class of 2020 at University of PGRI Sumatera Barat. Interviews were conducted with 10 students in English Education class of 2020. From the questionnaire distributed by researcher, it was found that mostly students chose to strongly agree with each statement given. Thus, researcher concluded that the students response on learning media by using videos received good response or a positive response. This is supported by the result of interviews conducted by researcher, students gave a good response to learning using videos. Because according to the students, learning using videos can increase their high willingness to learn, learning using videos is very interesting and learning using videos can improve critical thinking skills and the truth in expressing opinions.